The Chalcogen Exchange: The Replacement of Oxygen with Sulfur and Selenium to Boost the Activity of Natural Products - Muhammad Jawad Nasim; Wesam Ali; Eufrânio N. da Silva Júnior; Rahman Shah Zaib Saleem; Caroline Gaucher; Jadwiga Handzlik; Silvana Pedatella; Claus Jacob (Sci)
Antioxidants, such as stilbenes, anthocyanidins, coumarins, tannins and flavonoids, are often based on oxygen-containing redox systems and tend to feature several hydroxyl groups in their chemical structures. From a synthetic perspective, oxygen atoms are prone to bioisosteric replacement with sulfur and, notably, selenium. The main objective of this narrative literature review is to explore if and how bioisosteric substitution of oxygen with sulfur or selenium can enhance the biological activity of natural products. This replacement boosts the biological activity of the resulting molecules considerably as they now combine the redox and antioxidant properties of the original flavonoids and other natural products with the specific redox behavior of sulfur and selenium. Besides sequestering free radicals and peroxides, they may, for instance, also catalyze the removal of oxidative stressors, capture free metal ions and even provide scope for selenium supplementation. Since these molecules resemble their natural counterparts, they also exhibit considerable selectivity inside the body and a good pharmacokinetic profile. Still, the synthesis of such hybrid molecules integrating sulfur and selenium into flavonoids and other natural products is a challenge and requires innovative synthetic strategies and approaches.